Evaluation of the best vaccination regimen against Gumboro disease, based on the histopathologic lesions of bursa of Fabricius, in broilers - BOUYIOUKLIS (Π. ΜΠΟΥΓΙΟΥΚΛΗΣ), B.; LEKKAS (Σ. ΛΕΚΚΑΣ), S.; GEORGOPOULOU (Ι. ΓΕΩΡΓΟΠΟΥΛΟΥ), I.; IORDANIDIS (Π. ΙΟΡΔΑΝΙΔΗΣ), P. (Journal of the Hellenic Veterinary Medical Society, 2018)
For the evaluation of the best vaccination regimen against Gumboro disease using the vaccine strain D-78, based on the histopathologic lesions of bursa of Fabricius, 5 groups of experimental animals (A, B, C, D, E) of 15 chicks each were used. The chicks of group Β received the D-78 vaccine strain with the drinking water at the age of 14 days, those of C at the age of 8 and 11 days, and those of D at the age of 8 and 16 days, while the chicks of the other groups (A and E) remained unvaccinated. In the following, the chicks of the A, B, C and D groups were infected with a field strain of Gumboro disease virus, while those of E remained unvaccinated and uninfected as a control group. After 10 days, all chicks were killed and their bursae examined histological. It was established that the histopathologic lesions to the bursae of group C chicks were of a slighter degree than those of all the other challenged groups and therefore the protection to bursa of Fabricius against the disease is better with this vaccination regimen.